Крупномасштабные особенности полей температуры и солености на поверхности океана по данным 7-й Украинской антарктической экспедиции - Артамонов, Ю.В.; Перов, А.А. (Український антарктичний журнал, 2003)
On the basis of the hydrological data received during the 7th Ukrainian Antarctic Expedition in January-March, 2002, the large-scale peculiarities of the temperature and salinity fields of the sea surface in the Atlantic Ocean and Mediterranean sea are described. Sea surface front peculiarities are discussed. Seasonal changes of hydrological parameters in the tropical and middle latitude of the Atlantic Ocean were determined.